A study on implementing the mobile learning application on PDA in UiTM, Shah Alam / Nor Barina Mohd Mustafa - Mohd Mustafa, Nor Barina (2004)
This research is aimed at studying the implementation of M-learning application on PDA. The purpose of the study is to explore the innovative way of learning that can be implemented in UiTM, Shah Alam. This research focuses on analyzing the important requirements to implement M-Iearning, which also considering the interface design issues regarding on implementing the M-learning on mobile device such as PDA. The study showed that the implementation of the Mlearning may give much benefit to the students. Besides, most students have not much time to have their study, and students are prefer to have an interface design that meet user requirements. There are some suggested recommendations for this study. It is hoped that a lab session could be provided to ease students learn how to use a PDA. In addition, supports and encouragement from the government may lead to the success of the M-learning implementation. Hopefully, students will increase their interest on having M-learning and get a better understanding on the M-learning implementation